Primary geography - Scoffham, Stephen; Bridge, Colin (HarperCollins Publishers, 2014)
Description: Collins Primary Geography has been developed to provide full coverage of the national curriculum requirements for geography in the primary school. The Key stage 1 primary geography book delivers a progressive, skills based scheme for the early primary years. Subject specific vocabulary is introduced along with geographical skills to increase locational awareness. It covers map skills, physical, human and environmental geography, introduces contrasting localities in the UK, Europe, Asia and the wider world and uses an extensive range of evidence to stimulate the pupil’s interest and encourage investigative skills. Photographs, maps, satellite images artwork, charts and diagrams are use throughout. The pupil book has an accompanying teacher’s guide which contains copymasters.